2002
DOI: 10.1177/0892705702015003438
|View full text |Cite
|
Sign up to set email alerts
|

Impact Damage Resistance of Random Fiber Reinforced Automotive Composites

Abstract: Low-energy impact characteristics of four different random E-glass fiber reinforced thermoplastic and thermosetting matrix composites are studied. Low-energy impact causes dent on the impacted side and surface cracks on the unimpacted side of all four composites. The damage size, maximum impact load, deflection at the maximum load and tup velocity dissipation of the four composites are compared. The residual tensile strength of the impact-damaged composites is also determined as a function of the input impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Sadasivam and Mallick 46 have studied the lowenergy impact characteristics of four different E-GF reinforced thermoplastic and thermosetting matrix composites. Low-energy impact caused dent on the impacted side and surface cracks on the unimpacted side of all four composites.…”
Section: Laminate Thickness Layup and Stitchingmentioning
confidence: 99%
“…Sadasivam and Mallick 46 have studied the lowenergy impact characteristics of four different E-GF reinforced thermoplastic and thermosetting matrix composites. Low-energy impact caused dent on the impacted side and surface cracks on the unimpacted side of all four composites.…”
Section: Laminate Thickness Layup and Stitchingmentioning
confidence: 99%
“…Composites can be a great replacement to metals and alloys in many applications due to their unique combination of properties. [1][2][3][4] Composites are materials made up of multiple components that work together to create a material with superior properties. Some examples of composites that are being used as replacements for metals and alloys include carbon fiber reinforced polymer (CFRP) composites, glass fiber reinforced polymer (GFRP) composites, and ceramic-matrix composites (CMCs).…”
Section: Introductionmentioning
confidence: 99%
“…These materials provide the flexibility in designing of innovative systems and damage tolerant structures subjected to high differences in strain rate, pressure, and temperature . In the literature, the extensive studies on impact behavior of composite laminates can be found with variety of experimental, numerical, and analytical approaches . It is well known that composite materials are vulnerable to damage resulting from foreign objects due to the inherent brittleness of both the fiber and the matrix.…”
Section: Introductionmentioning
confidence: 99%